A Study on the Shaping and Practice of Social Roles Among Female Students in Wuhan's Church-Affiliated Schools During the War of Resistance Against Japan: The Case of Wuhan Church Girls' Middle School - JIANG, Yun (Journal of Research for Christianity in China (JRCC), 2025)
The outbreak of the War of Resistance against Japan shattered the previously stable educational environment. To preserve the flame of education, Wuhan Church Girls' Middle School chose the arduous path of relocating westward. Under these temporal and spatial conditions, the multiple social roles of the Wuhan Church Girls' School students—as female citizens, new women, and Christians—came into sharp focus. The formation of these multifaceted roles stemmed primarily from the era's environmental factors, the caring consciousness of the school's leadership, the awakening of the students' national and ethnic consciousness alongside the establishment of feminist liberation ideals, and the influence of the church, government, and societal forces on the school's development. These multifaceted social roles vividly illustrated the transition of church female students from traditional domestic roles toward broader and deeper societal roles. They embodied the integration of group identity, national identity, and religious identity within the church female student community.
Keywords: The War of Resistance Against Japan; Wuhan; Church Girls' High School; Social Role